Open Source Approaches in Spatial Data Handling - Leahy, Michael G. (Springer, 2017)
The role open-source geospatial software plays in data handling within the spatial information technology industry is the overarching theme of the book. It also examines new tools and applications for those already using OS approaches to software development.